Respostas

2013-05-14T23:00:48-03:00

3(5-2x) - 4(x+4) - 18 = 5x-10 

15 -6x - 4x - 16 - 18 + 10 = 5x

15 -10x - 24 = 5x

-9 = 15x

x = -3/5

1 5 1
2013-05-14T23:08:45-03:00

3( 5- 2x ) - 4 (x+4) - 18 = 5x -10    aplicando a distributiva nos parenteses

15 - 6x  - 4x - 16  - 18 = 5x - 10     organizando a equação juntando termos semelhantes

 -10x   -19                    = 5x - 10 

  -10x - 5x                      = - 10 +19

                     -15x           = 9 ( multiplicando por -1 )

                               15x  = -9

                                   x = -9/15

                                   x = -3/5